Improvements to the accuracy of prototype ship models measurement method using terrestrial laser scanner. (March 2017) - Abbas, Mohd Azwan; Lichti, Derek D.; Chong, Albert K.; Setan, Halim; Majid, Zulkepli; Lau, Chong Luh; Idris, Khairulnizam M.; Ariff, Mohd Farid Mohd
Abstract: Accuracy is a crucial requirement in the shipbuilding industry, especially during the design stage. The existence of errors in 3D prototype models can cause huge discrepancies when projected to full-scale objects. The ability to provide rapid and dense 3D data has made the terrestrial laser scanners (TLSs) a viable option in shipbuilding measurement. However, the numerous sources of systematic error that corrupt collected TLS data make a calibration procedure necessary. The requirement of laboratory with large number of targets to perform existing TLS calibration procedures make them unfeasible for most TLS users. Thus, this study has investigated the suitability of an on-site calibration method for application in high-accuracy shipbuilding. Two prototype boats were measured using a Faro Focus 3D scanner and close range photogrammetry was used for benchmarking purposes. By utilising four quantitative analyses, the results verify the ability of the developed calibration method to improve the accuracy of terrestrial laser scanner measurements in the field. With a relatively simple implementation, the developed calibration method is expected to be valuable for a wide variety of terrestrial laser scanner applications, especially the shipbuilding industry.